2018
DOI: 10.1136/bmj.k4168
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk, incident stroke, and the benefits of adhering to a healthy lifestyle: cohort study of 306 473 UK Biobank participants

Abstract: ObjectiveTo evaluate the associations of a polygenic risk score and healthy lifestyle with incident stroke.DesignProspective population based cohort study.SettingUK Biobank Study, UK.Participants306 473 men and women, aged 40-73 years, recruited between 2006 and 2010.Main outcome measureHazard ratios for a first stroke, estimated using Cox regression. A polygenic risk score of 90 single nucleotide polymorphisms previously associated with stroke was constructed at P<1×10−5 to test for an association with incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
189
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(210 citation statements)
references
References 32 publications
18
189
2
1
Order By: Relevance
“…Recent work has highlighted the potential of genomic risk scores (GRS) for risk prediction of common diseases [21][22][23][24] . Genomic risk prediction has a notable advantage over established risk factors as it could be used to infer risk of disease from birth, thus allowing the initiation of preventive strategies before conventional risk factors manifest and their discriminative capacity begins to emerge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has highlighted the potential of genomic risk scores (GRS) for risk prediction of common diseases [21][22][23][24] . Genomic risk prediction has a notable advantage over established risk factors as it could be used to infer risk of disease from birth, thus allowing the initiation of preventive strategies before conventional risk factors manifest and their discriminative capacity begins to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…For stroke, a recent 90-SNP GRS derived from the MEGASTROKE GWAS metaanalysis 4 showed that genetic and lifestyle factors are independently associated with incident stroke 24 , and that even among individuals with high GRS, lifestyle factors had a large impact on risk, implying that risk could be reduced in those with high genetic predisposition for stroke. However, in contrast to GRSs for other cardiovascular diseases like coronary artery disease (CAD) [21][22][23] , the predictive power of previous GRS for stroke has been limited [25][26][27] , likely because of limited genetic data for stroke and the well-known heterogeneity of the stroke phenotype 4,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The whole-genome approach to G-C interaction also sets this study apart from G-C interaction studies using a candidate gene approach which only focused on genetic variants with large phenotypic effects (e.g. [13][14][15] ). In these studies, variants might be missed if they contribute to GxE interaction and their effects depend on lifestyle factors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, G-C interaction estimates for cardiovascular traits are based on a limited number of genetic variants [13][14][15][16][17][18][19][20] ; therefore they are likely underestimated. R-C interaction has been largely neglected, leading to potential confounding between G-C and R-C interactions, in the presence of genuine R-C interaction 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Excessive alcohol use, smoking, and lack of physical activity are typical risk factors of lifestyle, which may contribute to adiposity, fatty deposition in the liver and increased all-cause mortality [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%